Application Of Business Principles Insurance In Indonesia - B. Parera, Agustinus; Tumanggor, M.S (Dinasti Research, 2021)
The insurance business in Indonesia, occurs in line with the expectations and challenges of the development of the non-bank insurance financial industry must deal with the problem of the world pandemic covid 19 because of the will of nature, related to the condition of the rill business that must be faced even often occurs in business people who are in the insurance world. This requires that business people must hold firm to the so-called prinsisip - principles or principles - insurance principles there are six principles, among others (1) Utmost Good Faith, (2) Insurable Interest, (3) Idemnity, (4) Subrogation, (5) Contribution,(6) Follow The Furtune Losses can occur between both parties, need balance(equality),equally and not true viewed from the side of the insured and the insurer himself, against violations that occur on the principles of insurance law, namely the principle of Utmost Good Faith,the etiquette of trueperfection, here is sometimes difficult to realize (integrity). In fact, because business people are humans not robots. Followed by the principle of Insurable Interest here it is important that there is no element of gambling (try - try / speculation), gambling for profit. The author argues that the two main and most important principles are barometer indicators for theinsurancebusiness, followed or supported by the four (4) principlesthat are interconnected or related and mutually supported against one principle with another, there are even other unnecessary principles, such as indemnity becauseit is not lifeinsurance. Therefore, it should be that a fair or good insurance business musthold firm to thesix principles of insurance law mentioned above, but the first principle (1) and second (2) are the main and most important legal principles and must be enforced to achieve justice(iustum)for the parties.